Gastrointestinal Symptoms in a Sample of Children with Pervasive Developmental Disorders - Nikolov, Roumen N.; Bearss, Karen E.; Lettinga, Jelle; Erickson, Craig; Rodowski, Maria; Aman, Michael G.; McCracken, James T.; McDougle, Christopher J.; Tierney, Elaine; Vitiello, Benedetto; Arnold, L. Eugene; Shah, Bhavik; et al. (Journal of autism and developmental disorders, 2009)
Objective To evaluate gastrointestinal (GI) problems in a large, well-characterized sample of children with pervasive developmental disorders (PDDs). Methods One hundred seventy two children entering one of two trials conducted by the Research Units on Pediatric Psychopharmacology (RUPP) Autism Network were assessed comprehensively prior to starting treatment and classified with regard to GI symptoms. Results Thirty nine (22.7%) were positive for GI problems, primarily constipation and diarrhea. Those with GI problems were no different from subjects without GI problems in demographic characteristics, measures of adaptive functioning, or autism symptom severity. Compared to children without GI problems, those with GI problems showed greater symptom severity on measures of irritability, anxiety, and social withdrawal. Those with GI problems were also less likely to respond to treatment.